2003
DOI: 10.1111/1467-8543.00270
|View full text |Cite
|
Sign up to set email alerts
|

Work–Life Imbalance in Call Centres and Software Development

Abstract: The paper evaluates the centrality of work to employees in two growing employment sectors, call-centres and software development. It then examines evidence for extensions of work into household and family life in these two sectors. Extensions are identified as tangible, such as unpaid overtime, or intangible, represented by incursions imported from work, such as exhaustion and stress. The study finds that organizational pressures, combined with lack of work centrality, result in work intruding into non-work ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
85
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 20 publications
3
85
0
1
Order By: Relevance
“…Again, we found that in the non-Western cultural context of India, hope was positively and significantly re- Another theoretical contribution, especially for the BPO industry, is to link hope to non-productive aspects of organizational environments. The counter-productive challenges (Hyman et al, 2003) workers faced may influence lesser levels of performance. From this study, we might infer relationships between counter-productive factors (e.g., burnout) and components of the hope construct.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Again, we found that in the non-Western cultural context of India, hope was positively and significantly re- Another theoretical contribution, especially for the BPO industry, is to link hope to non-productive aspects of organizational environments. The counter-productive challenges (Hyman et al, 2003) workers faced may influence lesser levels of performance. From this study, we might infer relationships between counter-productive factors (e.g., burnout) and components of the hope construct.…”
Section: Discussionmentioning
confidence: 99%
“…The social and political conditions of India and the working conditions BPO workers experience give rise to examining the methods and mechanisms that may enhance individual and organizational performance. Performance issues are seriously impacted by overarching characteristics of the work environment including high levels of attrition, low job satisfaction and commitment, a high degree of worker burnout, and concerns for effective work-life balance (Hyman et al, 2003;Taylor & Bain, 2005). In this study, hope is shown to be highly related to performance as measured by commission and supervisor ratings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations